Analisis Komposisi Sedimen di Unit Pengolahan Limbah Kota Padang - Ummi, Sodaya; Zulkarnaini; Indah, Shinta (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The purpose of this study is to identify factors that affect environmental parameters in sediments and their impact on sewage treatment plant in Padang city in order to become a basic scientific reference in effective and sustainable water resources management. The measurements were carried out at 5 artificial system locations, namely the Rubber Factory Wastewater Treatment Plant (WWTP), Tofu Factory wastewater drainage, WWTP of Teaching Hospital Andalas University, Fecal Sludge Treatment Plant, and Leachate Treatment Plant at the Air Dingin of Landfill in Padang City, West Sumatra. The measured water parameters are pH, temperature, and salinity, while the measured sediments are nitrite and nitrate. Analysis of environmental parameters in the waters were temperature (30 - 34°C), pH (5.5 - 6.8), and salinity (0 ± 0.4 ppt). The results obtained in the sediment were nitrite (0.63 - 153.58 mg/L), and nitrate (19.28 - 50.01mg/L). Factors that affect water and sediment parameters are biological activity and anthropogenic contaminants. One of the causes of high concentrations of environmental parameters in sediments is the ability of sediments to accumulate and absorb particles and chemicals.